Święty Alfons M. de Liguori i święty Paweł od Krzyża –nauczyciele medytacji męki Chrystusa - Kotyński, Marek (Warszawskie Studia Teologiczne, 2019)
Meditation seems to be a modern phenomenon today, meanwhile its roots go back to antiquity and for centuries it was developed and nurtured in the Church as a way of union with God. Saint Paul of the Cross and Saint Alphonsus Maria de Liguori, the most significant Saints of the Enlightenment, contributed to the fact that it did not become only an “era of reason” closed to grace, an era of deism, naturalism, religious indifferentism and mocking criticism of the Church. Both Saints brightened their times thanks to the fervent meditation of the Passion of Christ, lived in faith, hope and love. They then made their spiritual experiences a source of inspiration for others. As missionaries, retreat masters and spiritual writers, they devoted themselves to opening minds and hearts of many to supernatural grace by considering the incredible love of God revealed on the Cross. The article shows how the charism and commitment of both Saints found their articulation in the wise meditation practices and extensive mission systems proposed to the faithful in order to support their journey to holiness as well as their unity with the One who is the Way, the Truth and the Life.